A Putative Curcumin Biosynthetic Pathway in Musa textilis Née (Abaca) - Balinado*, Lloyd Ongpauco (Asian Journal of Biological and Life Sciences, 2026)
Curcumin is a diarylheptanoid compound extensively documented in Curcuma species (Zingiberaceae) and valued for its diverse pharmacological properties. To date, curcumin has not been reported as a naturally occurring metabolite in members of the genus Musa (Musaceae). In this study, we investigated the potential for curcumin biosynthesis in Musa textilis (abaca) through integrative analysis of available genomic and transcriptomic datasets. Using KEGG-based pathway reconstruction, we identified putative homologs of key enzymes involved in diarylheptanoid biosynthesis, including Diketide-CoA Synthase (DCS) and Curcumin Synthase (CURS), in the genomes of M. textilis var. Abuab and M. balbisiana. Transcriptomic data further revealed the expression of diarylheptanoid-associated genes across multiple M. textilis genotypes. While direct chemical detection of curcumin was not performed, these findings provide molecular evidence suggesting the presence of a putative curcumin biosynthetic pathway in M. textilis. This work expands current understanding of secondary metabolism in abaca and highlights the need for targeted metabolomic validation.
Keywords: Abaca; Curcumin; Diarylheptanoid; Musa textilis; Secondary metabolism